Iron, ferroptosis, and ischemic stroke - Guo, Jun; Tuo, Qing‐zhang; Lei, Peng (Journal of neurochemistry, 2023)
Over 30 million people suffer from the consequences of ischemic stroke. The precise molecular mechanism of neuronal damage during ischemic stroke remains unclear; therefore, the effective treatment of post‐ischemic stroke remains a critical challenge. Recently, iron has emerged as a crucial factor in post‐reperfusion injuries, participating in cell peroxidation, excitotoxicity, and a distinctive cell death pathway, namely, ferroptosis. Since iron is tightly regulated in the brain and important for brain functions, the imbalance of its metabolism, including its overload and deficiency, has been shown to impact ischemic stroke outcomes. This review summarizes the current understanding of pathological events associated with iron in ischemic stroke and discusses relevant drug development. Ischemic stroke caused by arterial occlusion is the most common type of stroke, and it strongly associates with age‐related neurological deficits. Recently, iron has emerged as a crucial factor of neuronal pathology in ischemic stroke. Iron dyshomeostasis leads to brain iron accumulation, and together with the excessive production of free arachidonic acid, insufficient antioxidant supply, they collectively induce lipid peroxidation and ferroptosis during cerebral ischemia/reperfusion. Independently or co‐currently, peripheral iron deficiency also aggravates the cerebral ischemic injury. This review summarizes the current understanding of pathological events associated with iron in ischemic stroke and discusses relevant drug development. ACSL4, acyl‐CoA synthetase long‐chain family member 4; GPx4, glutathione peroxidase 4; LOX, lipoxygenase.